2018
DOI: 10.1002/ep.12954
|View full text |Cite
|
Sign up to set email alerts
|

Development of fungal consortium for the pretreatment of rice straw under optimized solid state and shake flask conditions

Abstract: Three consortia were developed out of the ligninolytic fungal isolates for pretreatment of rice straw. The fungal consortium of Pleurotus ostreatus and Phanerochaete chrysosporium, produced maximum laccase (Lac), lignin peroxidase (LiP), and manganese peroxidase (MnP) activities of 2.40 nkat/gds, 37.92 nkat/gds, and 62.50 nkat/gds, respectively. Response surface methodology (RSM) based on central composite design (CCD) was used to optimize pretreatment of rice straw under solid state conditions. With a desirab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 43 publications
0
12
0
1
Order By: Relevance
“…ostreatus S18 coculture also achieved a twofold lignin degradation rate 13 . Recently, Kaur et al 14 reported a maximum laccase (Lac), lignin peroxidase (LiP), and manganese peroxidase (MnP) activities of 2.40 nkat/gds, 37.92 nkat/gds, and 62.50 nkat/gds respectively using P . ostreatus and P .…”
Section: Introductionmentioning
confidence: 99%
“…ostreatus S18 coculture also achieved a twofold lignin degradation rate 13 . Recently, Kaur et al 14 reported a maximum laccase (Lac), lignin peroxidase (LiP), and manganese peroxidase (MnP) activities of 2.40 nkat/gds, 37.92 nkat/gds, and 62.50 nkat/gds respectively using P . ostreatus and P .…”
Section: Introductionmentioning
confidence: 99%
“…Remazole brilliant blue R is structurally similar to lignin backbone, which was efficiently decolorized by WRF‐secreting ligninozymes. In our laboratory, Kaur et al 11 . recorded LI readings of 2.4 and 2.2 for P. ostreatus and P. chrysosporium , respectively.…”
Section: Resultsmentioning
confidence: 85%
“…The synergistic effect of Lacc, LiP, and MnP as a fungal consortium for paddy straw pretreatment is in agreement with previous reports. Pretreatment of paddy straw with concentrated fungal ligninolytic enzymes resulted in 80.87% and 47.64% lignin and hemicellulose reduction, respectively, with a 29.96% rise in the proportion of cellulose 11 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tobacco stalk substrate treated with T. hirsuta S13 and P. ostreatus S18 coculture also achieved a 2-fold lignin degradation rate (from 23.7 to 41.1%) 8 . Recently, Kaur, et al 9 reported a maximum laccase (Lac), lignin peroxidase (LiP), and manganese peroxidase (MnP) activities of 2.40 nkat/gds, 37.92 nkat/gds, and 62.50 nkat/gds respectively via a Pleurotus ostreatus and Phanerochaete chrysosporium fungal consortium on rice straw. These independent studies demonstrate the potential of white-rot fungal consortium to alter cell wall chemical constituents of various straw via their enzyme activities/secretions.…”
Section: Introductionmentioning
confidence: 99%